Republic of Armenia : Staff Report for the 2001 Article IV Consultation and Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper assesses the Republic of Armenia's 2001 Article IV Consultation and a Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF). The economic situation in Armenia has improved since mid-2000 following the deterioration in late 1999 and early 2000. Real GDP began to recover in the second quarter and increased by 6 percent for 2000 as a whole. The authorities have made progress in reforming the energy sector, which remains a considerable financial drain on the budget and the rest of the economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet